Trans-2-hexen-1-ol as a tool for the control of Fusarium verticillioides in stored maize grains. (June 2019) - Brito, Vanessa Daniela; Achimón, Fernanda; Dambolena, José Sebastian; Pizzolitto, Romina Paola; Zygadlo, Julio Alberto
Abstract: Fusarium verticillioides infects stored maize grains. In the present study, we first evaluated the effects of ten volatile organic compounds on F. verticillioides growth in culture medium. Subsequently, based on the antifungal activity obtained in the present study and the insecticidal effect against Sitophilus zeamais reported previously, trans-2- hexen-1- ol was selected to analyzed its effect on the fungus in stored maize. All the compounds tested showed inhibitory activity on fungal development, being the most active compounds geraniol, nerol, isovaleraldehyde and linalool, followed by trans-2-hexen-1-ol, cis-3-hexen-1-ol, cis-2-hexen-1-ol and trans-3-hexen-1-ol. Besides its antifungal activity against F. verticillioides, trans-2-hexen-1-ol inhibited FB1 production. In this study it was also demonstrated that S. zeamais favors F. verticillioides dispersion, confirming the importance of these insects as mechanical vectors of fungal spores. These results reveal the ability of trans-2-hexen-1-ol as a potential tool to control F. verticillioides in a natural approach as an alternative to synthetic pesticides. Highlights: Nerol, geraniol and linalool showed highest effect against Fusarium verticillioides . Isovaleraldehyde was the most active aldehyde against F. verticillioides . Trans-2-hexen-1-ol showed effect on Fusarium and on its dispersion by weevils.